2016
DOI: 10.1007/s10973-016-5588-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of antiwear CrN coating thickness on the evolution of thermomechanical interactions in the substrate/PVD coating system

Abstract: The main goal of this study was to analyze the application possibilities of modulated temperature thermomechanical analysis (MT TMA) for the evaluation of thermomechanical interactions in substrate/PVD coating systems on the example of examination of influence of changes in thickness of a coating on internal stress evolution in these systems. As an indicator of the stress state in the coating at a given measurement temperature, the changes in a value of the equivalent thermal expansion coefficient of the syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Particular interest in this area is directed towards the coating on the base of chromium nitride. These coatings are, among other, characterised by relatively low value of residual stress and good resistance to oxidation at high temperatures (Gauzzi et al, 2008;Lee et al, 2001;Mydłowska et al, 2016). For monolayer coatings deposited by PVD techniques, it is often observed that increasing the hardness of the coatings is accompanied by a simultaneous increase in the Young's modulus and decrease of their ductility (impact resistance), which leads to a reduction of coating's fracture toughness due to the reduction of their ability to dissipate mechanical energy (through plastic deformation).…”
Section: Introductionmentioning
confidence: 99%
“…Particular interest in this area is directed towards the coating on the base of chromium nitride. These coatings are, among other, characterised by relatively low value of residual stress and good resistance to oxidation at high temperatures (Gauzzi et al, 2008;Lee et al, 2001;Mydłowska et al, 2016). For monolayer coatings deposited by PVD techniques, it is often observed that increasing the hardness of the coatings is accompanied by a simultaneous increase in the Young's modulus and decrease of their ductility (impact resistance), which leads to a reduction of coating's fracture toughness due to the reduction of their ability to dissipate mechanical energy (through plastic deformation).…”
Section: Introductionmentioning
confidence: 99%
“…Coatings play an important role in many technological areas including thermal industries, manufacturing of gas turbine engines widely used in aerospace industry, industrial power generations, color sciences, insulation industries, solar cells, and marine applications. Providing a proper coating can enhance the performance and useful life of the system [1][2][3]. Moreover, most of metals are working under varying harsh conditions and environments.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords:, Computational materials science; Finite Element Method, Stress, Strain, Deformation, Anatomical surgical tweezers A contemporary technological development makes it necessary to look for new constructional solutions that aim at the improvement of the effectiveness and quality of a product, at the minimization of dimension and mass as well as the increasing of reliability and dimension stability in the operation conditions [1][2][3][4][5][6]. Tweezers are classified as picking tools consisting of two arms produced in a plastic working process and connected permanently by welding.…”
mentioning
confidence: 99%